THE INFLUENCE OF COACHING METHODS, ACADEMIC SUPERVISION, AND SCHOOL CULTURE ON WORK MOTIVATION: A QUANTITATIVE STUDY AT JUNIOR HIGH SCHOOLS IN LASEM, REMBANG - Pujoko; Rasiman; supandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the influence of the coaching method, academic supervision, and school culture on teacher work motivation in private junior high schools in Lasem District, Rembang Regency. The research employed a quantitative approach with an explanatory survey design. Data were collected using questionnaires distributed to 62 teachers from various private schools and analyzed through descriptive and inferential statistics using multiple linear regression. The results showed that, partially, the coaching method had a positive and significant influence on teacher work motivation with a contribution of 32.9%. Academic supervision also significantly affected teacher motivation with a contribution of 34.0%. Furthermore, school culture had a significant effect, contributing 32.8% to teacher motivation. Simultaneously, the three variables coaching, academic supervision, and school culture contributed 49.6% to the variance in teacher motivation. These findings indicate that improving teacher motivation requires an integrative approach. Coaching plays a crucial role in fostering professional awareness and reflection. Academic supervision enhances pedagogical competence through structured, constructive feedback. Meanwhile, a strong and supportive school culture fosters collaboration, trust, and teacher commitment. Therefore, synergy between personal, professional, and institutional support must be continuously strengthened to ensure optimal teacher performance and improve educational quality in private schools.